Game 2D “Gangguan Jalur Akses Optic Telkom” - Joan Neibel Ginting; Nelmiawati Nelmiawati (Politeknik Negeri Batam, 2020)
Material delivery to the maximum for new companies is accepted for the company. Maximum delivery of material is considered very important for all activities in the field carried out by employees for the company. Material that is considered lay must be conveyed well to the new employee. As a solution to the complexity, 2D games will be designed using the MDLC research method version of Luther-sutopo. In the development of this study, the authors focused more on the analysis of 2D game usability. The technique of collecting data to study the results is done by distributing questionnaires to employees of PT Telkom Batam Access as many as 30 respondents who were then analyzed from the results obtained as parameters of quality of use. The average results of respondents' responses get 87.4% categorized very well.